Antimicrobial and Wound Healing Activities of Three Cassia Species - Ismail, Elysha Nur (2004)
Cassia alata, Cassia fistula and Cassia auriculata are largely used in traditional medicine for centuries, to improve health and well being of human civilizations in rural areas of developing countries worldwide. The objective of this study is to investigate the antimicrobial and wound healing activities of all three Cassia species. The first two experiments were conducted to investigate the antibacterial and antifungal activities of three Cassia species using disc diffusion methods. Ethanol and aqueous extract of all three Cassia species were tested in vitro against the bacteria Escherichia coli, Salmonella enteritidis, Staphylococcus aureus and Bacillus subtilis, and the fungi, Candida albicans, Candida tropicalis, Microsporum canis and Aspergillus fumigatus. All three Cassia species were effective against Staphylococcus aureus and Bacillus subtilis in a dose dependent manner, and were not effective against Escherichia coli and Salmonella enteritidis. The results were compared with commercial antibiotics chloramphenicol (30 mg/ml), ampicilin (10 mg/ml), penicillin G (10 mg/ml), erythromycin (15 mg/ml), tetracycline (30 mg/ml) and enrofloxacin (5 mg/ml). All three plants were only effective against the Grampositive bacteria. The ethanol leaf extract of the plants at concentration 80 mg/ml can be compared to the commercial antibiotic, penicillin against Bacillus subtilis. Only Cassia alata and Cassia auriculata has exhibited antifungal activity. Cassia fistula has no effect against all tested fungi. The ethanol and aqueous bark extracts from Cassia alata was only effective against Candida albicans, whereas the ethanol leaf and bark extract from Cassia auriculata was only effective against Microsporum canis. When comparing the two plants against each other, we found that the plant extracts was selective and has a very narrow spectrum against the tested fungi. The ethanol leaves extracts from all Cassia species were chosen for the third test, which was the wound healing activity in mice. Topical application over an incised wound showed progressive infiltration of inflammatory cells, increased blood vessel formation, and enhanced proliferation of cells because of treatment with Cassia fistula extract and acriflavine. Wound contraction in specimens from the groups treated, respectively, with Cassia fistula, acriflavine and control, showed significant structural improvement when compared to Cassia alata and Cassia auriculata, in which there were no signs of healing at the end of the experiment. It can be concluded that, ethanol extracts of the leaf and bark of Cassia alata, Cassia fistula and Cassia auriculata showed antibacterial and antifungal activity which may be attributed to the presence of chemical constituent such as flavonoids, chrysophanol antharaquinones, and chrysarobin. This study also showed the promising wound healing activity of Cassia fistula in mice and warrants detailed experimental and clinical studies. It also provides a rationale for the use of Cassia fistula in preparations of traditional medicine to promote wound healing.